Technical efficiency estimates for Sarawak pepper farming: a comparative analysis - Radam, Alias; Ismail, Mohd Mansor (Universiti Putra Malaysia Press, 1999)
Estimating technical efficiency of production technology is important for policy purposes. Four production frontiers consisting of parametric and nonparametric functions were analysed to estimate technical efficiency ratios on a sample of pepper farms in Sarawak. The methodologies employed produced different estimates, distributions, and rankings of efficiency ratios. The nonparametric estimates were greater than parametric estimates except under stochastic parametric method. Due to the large differences in technical efficiency results, recommendation for policy purpose should not be made without prior detailed analysis of each method.